Analysis of zntA gene in environmental Escherichia coli and additional implications on its role in zinc translocation - Vidhyaparkavi, Anandhan (3 Biotech, 2017)
Escherichia coli strains from sewage sample were screened for the presence and expression of heavy metal-translocating zntA gene by PCR and RT-PCR analysis with type culture of K-12 as standard strain. The strain which showed high level of gene expression (SBVP1) was chosen to further study the growth and heavy metal translocation. This superior strain was grown in the presence of ZnSO(4), Pb (CH(3)COO)(2) and mixture of ZnSO(4), Pb(CH(3)COO)(2) metal salts and the growth was observed at different time points. The cell pellet fraction was found to have more of zinc than lead as determined by atomic absorption spectroscopy indicating the translocation of these metals from media to the cells. However, the intracellular translocation of zinc is affected by the presence of lead in the media. Expression of the zntA gene in bacteria grown in the presence of ZnSO(4) was also studied and the molecular analysis results correlate with spectroscopic observations.